Personal communication in an automated world: Evidence from loan repayments - Christine Laudenbach; Stephan Siegel (Leibniz Institute for Financial Research SAFE, 2024)
We examine the effect of personal, two-way communication on the payment behavior of delinquent borrowers. Borrowers who speak with a randomly assigned bank agent are significantly more likely to successfully resolve the delinquency relative to borrowers who do not speak with a bank agent. Call characteristics related to the human touch of the call, such as the likeability of the agent's voice, significantly affect payment behavior. Borrowers who speak with a bank agent are also significantly less likely to become delinquent again. Our findings highlight the value of a human element in interactions between financial institutions and their customers.
Keywords: D14; G11; 330; Personal Communication; Consumer Finance; Loan Repayment; Promise Keeping; Social Distance